Kajian Sosiologi Hukum tentang Perjanjian Pinjaman Uang dengan Bunga yang Tinggi: Ditinjau dari Teori Konflik Karl Marx: Penelitian - Herianto Sihombing; Rosmalinda Rosmalinda; Agusmidah Agusmidah (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
High-interest loan agreements are increasingly prevalent in society through formal and informal institutions, including online loans and loan sharks. While providing quick access to capital, this practice often creates economic inequality, increases debt risk, and worsens the socio-economic conditions of borrowers, particularly vulnerable groups. A sociological analysis of law is relevant to examining the relationship between law, economic practices, and social structures in the power relations between lenders and borrowers. This study uses Karl Marx's conflict theory to examine power dynamics, where lenders, as the bourgeoisie, exploit their economic position, while borrowers, as the proletariat, are subordinated due to limited access to information, capital, and financing alternatives. The study's results indicate that high-interest loans have the potential to become a means of exploitation, reinforcing bourgeois dominance and widening socio-economic inequality. Therefore, it is recommended to strengthen regulations on interest rates and oversight of illegal loans, improve financial literacy among vulnerable communities, and implement fair and transparent consumer protection to achieve more equitable and sustainable lending practices.